Governance Dilemmas in Canada, North America, and Beyond: A Tribute to Stephen Clarkson
IX, 167 p. 1 illus.
Keywords: This book discusses the development of Canadian political economy through the legacy of Stephen Clarkson, who for over 40 years analyzed the challenges that economic changes brought to the economic governance of Canada, North America, and the world. Tracing the main themes of Clarkson scholarship, it explores in four sections how changes in the global economy, such as regional and inter-regional trade agreements, impact the political economy of Canada and North America, the focus of most of Clarkson’s works, without leaving aside the rest of the world. The book is divided in four main sections that correspond to Clarkson’s scholarly contributions. The epilogue takes a personal tone and presents how the legacy of Stephen Clarkson serves as an inspiration for scholars facing a different world. Michèle Rioux is Professor at the Department of Political Science at the Université du Québec à Montréal, Canada. She is the Director of the Centre d’études sur l’intégration et la mondialisation. She recently co-edited Vers une politique commerciale socialement responsable dans un contexte de tensions commerciales (2021). Alejandro Angel is a postdoctoral researcher in the Graduate Program in International Relations at the Universidade Federal de Santa Catarina, Brazil. He holds a doctorate in political science from the Université de Montréal, Canda. He recently published Consolidating Economic Governance in Latin America (2021). Marjorie Griffin Cohen is a feminist economist who is Professor Emeritus of Political Science and Gender, Sexuality and Women’s Studies at Simon Fraser University, USA. She recently received the Galbraith Prize in Economics and Social Justice (2016), and the Charles Taylor Prize for Excellence in Policy Research (2020). Daniel Drache is Professor Emeritus of Political Science and Senior Research fellow, Robarts Centre for Canadian Studies, York University, Canda. His most recent book is One Road, Many Dreams: China's Bold Plan to Remake the Global Economy, co-edited with A.T. Kingsmith and Duan Qi (2019).